UPAYA MENINGKATKAN HASIL BELAJAR MELALUI CONTEXTUAL TEACHING AND LEARNING PADA KONSEP ALAT PENGUNGKIT BAGI SISWA SEKOLAH DASAR - Dewi Sinta (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2022)
This study aims to improve student learning outcomes using the Contextual Teaching and Learning (CTL) approach to the concept of levers in science lessons. The method used is action research in class V SDN 1 Sukakarya, Tarogong Kidul District, Garut Regency. This classroom action research was conducted in three cycles by taking the stages of planning, implementing action, observing, and reflecting. Student learning outcomes individually from cycle I, cycle II, cycle III, each cycle has increased. During the pre-cycle, the average student score on the concept of a lever was 34.66, then it increased in cycle I to 47.02, cycle II increased to 57.37 and cycle III increased to 79.71. Based on the results of the research that the application of the CTL approach can improve the learning outcomes of fifth grade students at SDN 1 Sukakarya on the concept of levers in science subjects.